Dividend Policy: The Impact of Financial Performance, Governance, and Managerial Ownership in Capital Markets - Tumiwa, John Calvin; Prayanthi, Ika; Rantung, Danny Ivan; Oroh, Nouke Sysca (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study explores the influence of financial performance, governance, and managerial ownership on dividend policy in companies listed on the Indonesia Stock Exchange. The main issue addressed is the ongoing controversy in the literature regarding how these factors affect Dividend Yield, given the inconsistencies in previous research. The study aims to examine the role of Retained Earnings, Return on Assets, the Board of Directors, Independent Commissioners, Managerial Ownership, and company size in shaping dividend policy. A quantitative approach is employed, using a regression method to analyse panel data from 400 companies over the period 2018–2022. The results indicate that Retained Earnings, Independent Commissioners, and Managerial Ownership have a significant impact on Dividend Yield, whereas Return on Assets, the Board of Directors, and Total Assets do not. The findings highlight the crucial role of strong governance in dividend policy, while Return on Assets, the Board of Directors, and firm size measured by Total Assets do not exhibit a significant effect. This study underscores the need for effective governance to minimize conflicts of interest and emphasizes the importance of considering local contexts when formulating dividend policies in Indonesia.